KEBERLANJUTAN KEGIATAN PENINGKATAN KUALITAS PRASARANA PERMUKIMAN KUMUH DI KELURAHAN KUNINGAN KOTA SEMARANG - Hafzhi Nur Azmi; S Sunarti (Jurnal Riptek, 2020)
Slum infrastructure improvement activities have been carried out in the Kuningan City of Semarang City from 2015 to 2018 focusing on improving the quality of roads and drainage in 23 ha of slum areas. The passive involvement of community institutions and some physical damage that was found are the background that makes research on the sustainability of these activities are matters. This research purpose is to measure the sustainability of slum infrastructure improvement activity  in the Kuningan District This study uses a quantitative approach by distributing questionnaires to 97 samples among 3211 KK and reviewing documents on data collection methods and scoring analysis on analytical methods. Based on the results of the study, it was concluded that the Slum infrastructure improvement activities in Kuningan District had been categorized as sustainable. Improvement on maintenance instensity, quantity and quality and improvement on public figure involvement  are needed to support its sustainability.